2022
DOI: 10.1021/acs.jpcc.1c09990
|View full text |Cite
|
Sign up to set email alerts
|

Charge Localization in Defective BiVO4

Abstract: We study the native defects in bismuth vanadate using hybrid density functional theory. We pay special attention to where excess charges localize by considering different polaronic distortions and find that charge localization has a profound effect on the local chemical environment around certain defects. In particular, oxygen dimerization may occur in the presence of acceptor defects. On the basis of Fermi level pinning due to compensation between donors and acceptors we additionally find that intrinsic p-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 53 publications
2
17
0
Order By: Relevance
“…The resulting relative formation energies are shown in Fig. 3a for chemical potentials corresponding to O-poor and Bi-rich conditions that are expected for n-type BiVO 4 according to a previous theoretical study by Österbacka et al 49 Formation energies for other chemical potentials are shown in Fig. S6.…”
Section: Resultsmentioning
confidence: 54%
“…The resulting relative formation energies are shown in Fig. 3a for chemical potentials corresponding to O-poor and Bi-rich conditions that are expected for n-type BiVO 4 according to a previous theoretical study by Österbacka et al 49 Formation energies for other chemical potentials are shown in Fig. S6.…”
Section: Resultsmentioning
confidence: 54%
“…This demonstrates that the oxygen vacancy systems are unstable compared to the pristine BiVO 4 system. 43 This can well explain the phenomenon of structure collapse caused by the oxygen vacancies in the experiment.…”
Section: Geometric Structurementioning
confidence: 62%
“…A possible origin of the differences between η sep obtained in each case may be related to the presence of structural defects, mainly oxygen vacancies, on the surface of BiVO 4 , as it has been extensively reported. [ 61–63 ] These defects can act as recombination centers, known as surface traps, that could ultimately decrease the η sep . [ 64–66 ] Indeed, surface recombination was reported as the main limiting process on the performance of BiVO 4 photoanodes.…”
Section: Resultsmentioning
confidence: 99%